Evidence of a dynamic fault model in the DICE radiation-hardened cell - da Cruz, William Souza; Dutertre, Jean-Max; Rigaud, Jean-Baptiste; Hubert, Guillaume (Symposium on Integrated Circuits and Systems Design (SBCCI), 2020)
Hardware redundancy techniques are routinely used for mitigation purposes in radiation-hardened integrated circuits. Duplication indeed has been proved effective to harden the well known dice memory cell against seus. In this work, we nonetheless report, on simulation basis, the possibility of a dynamic fault mechanism that may turn an set into an error. We also introduce and validate a countermeasure that alleviates this weakness.